2006
DOI: 10.1055/s-2006-926380
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of 1,3-Dibromo-5,5-dimethylhydantoin (DBH) in the One-Pot Transformation ofN-Arylglycines toN-Arylsydnones in the Presence of NaNO2/Ac2O under Neutral Conditions: Subsequent Bromination of these Sydnones to their 4-Bromo Derivatives

Abstract: 1,3-Dibromo-5,5-dimethylhydantoin (DBH) has been found to efficiently catalyze the one-pot conversion of various Narylglycines through N-nitrosation and cyclization to sydnones in combination with NaNO 2 and Ac 2 O in high yields (80-94%) under mild and neutral conditions. Also, it was shown that DBH can conveniently promote the bromination of these sydnones to their 4-bromo substituted congeners in excellent yields in DMF at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Azarifar and Ghasemnezhad-Bosra reported that DBH is capable of brominating sydnones to their 4-bromo-substituted congeners in excellent yields in DMF at room temperature (Scheme ). Initially, they developed a method for the conversion of various N -arylglycines to sydnones using the same reagent in the presence of sodium nitrite and acetic anhydride in dichloromethane. Bromination of the resulting sydnones was carried out using 2 mol equiv of DBH.…”
Section: Bromination Reactionsmentioning
confidence: 99%
“…Azarifar and Ghasemnezhad-Bosra reported that DBH is capable of brominating sydnones to their 4-bromo-substituted congeners in excellent yields in DMF at room temperature (Scheme ). Initially, they developed a method for the conversion of various N -arylglycines to sydnones using the same reagent in the presence of sodium nitrite and acetic anhydride in dichloromethane. Bromination of the resulting sydnones was carried out using 2 mol equiv of DBH.…”
Section: Bromination Reactionsmentioning
confidence: 99%
“…45 Bromination has been achieved with Br 2 /NaHCO 3 , 46 Br 2 /Ac 2 O, 47 KBrO 3 /HBr, 41 N -bromosuccinimide (NBS), 48 or 1,3-dibromo-5,5-dimethylhydantoin (DBH). 49 Finally, direct iodination of sydnones has been described with N -iodosuccinimide (NIS) in AcOH, 50 or ICl in AcOH. 51…”
Section: Resultsmentioning
confidence: 99%
“…46 Finally, one-pot strategies were developed, avoiding the isolation of the toxic nitroso-amine intermediate. 47,48 In 2019, an alternative method using mechanochemistry was developed by the group of Lamaty. 49 Interestingly, the sydnone core offers various postfunctionalization possibilities, which have been the topic of several works, including reviews (Scheme 6b).…”
Section: Structure and Properties Of Mesoionicsmentioning
confidence: 99%
“…The nitrosylation step was also improved by Turnbull by using isoamyl nitrite, a milder reagent which requires only evaporation as workup . Finally, one-pot strategies were developed, avoiding the isolation of the toxic nitroso-amine intermediate. , In 2019, an alternative method using mechano-chemistry was developed by the group of Lamaty . Interestingly, the sydnone core offers various postfunctionalization possibilities, which have been the topic of several works, including reviews (Scheme b). , Indeed, the proton in position C 4 possesses an acidic character and can be abstracted in the presence of different organometallic species.…”
Section: General Information On Mesoionicsmentioning
confidence: 99%